Spatial orientation of trout (Salmo trutta L.) and rainbow trout (Oncorhynchus mykiss Walb.) embryos in natural and artificial magnetic fields - K. Formicki; M. Bonisławska; M. Jasiński (Acta Ichthyologica et Piscatoria, 1997)
Trout (Salmo trutta L.) and rainbow trout (Oncorhynchus mykiss Walb.) embryos developing in eggs incubated in the geomagnetic field are oriented NW-SE. Artificial horizontal magnetic fields of 0.5 and 1.0 mT, i.e., higher than that of the natural one but of the same direction resulted in a changed alignment of the embryos examined. The embryos placed in those artificial fields were aligned N-S and NE-SW. A 90° clockwise rotation of the artificial horizontal magnetic field poles, relative to the geomagnetic one, resulted in embryos′ orientation being changed to N-S and NE-SW.